Temperature dependence of elastic properties of aluminium foam structures - Hosseini, Seyed Mohd. Hossien (Trans Tech Publications, 2012)
The temperature dependence of mechanical properties of aluminum foams has been investigated. Young's modulus and Poisson's ratio have been determined from simulations of a unidirectional tensile test using a finite element model of aluminum foam networks. The Young's modulus of the network structure for different relative densities and foam cell regularity factors have been plotted over temperature. It has been found that the Young's modulus decreases with increasing temperature, whereas the Poisson's ratio remains constant. This trend has been observed for various foam structures of different sizes, relative densities and network irregularities.